Navigation Ranging Scheme Based on Microwave-Optical Entanglement Prepared by Electro-Opto-Mechanical Converters - Junwen Luo; Dewei Wu; Qiang Miao; Chunyan Yang; Tianli Wei (IEEE Photonics Journal, 2020)
Microwave is widely used in present navigation system. It works well, yet it faces precision limit and other challenges. Quantum entanglement has been applied in various fields and resulted in quite remarkable improvements, especially in precision performance. Hence, we attempt to apply quantum entanglement to enhance merits of navigation system performed in microwave regime. This paper introduces principles of microwave-optical entanglement prepared by electro-opto-mechanical converters in detail. Meanwhile, a navigation ranging scheme exploiting this type of entanglement is proposed. The performance of the scheme is analyzed, and factors influencing entanglement feature and ranging feature are discussed. It shows that the ranging scheme has achieved quite precise results with help of microwave-optical entanglement, and it may be regarded as a promising candidate of new navigation ranging scheme.